A critical analysis on the law of establishment of kindergarten in protecting children's safety in kindergarten premises in Shah Alam, Selangor / Muhammad Nizamuddin Abdul Hamid, Muhamad Nur Shariman Muhamad Radzi and Muhammad Hameezy Mokhtar - Abdul Hamid, Muhammad Nizamuddin; Muhamad Radzi, Muhamad Nur Shariman; Mokhtar, Muhammad Hameezy (2007)
This research was conducted for the purpose of examining all the relevant laws which govern the establishment of kindergarten in Shah Alam and to provide the conclusion on to the extend of safety protection given under the law given to the children in kindergarten premises. This topic was chosen due to the many numbers of kindergartens established in Shah Alam and the importance of protecting the safety of the children's in the kindergarten premises. The fact that there are many accidents involving children's in the kindergarten in Malaysia also triggers us to conduct this research. Therefore the discussion on this matter would provide future benefit of legal and social development in the areas involved.